The JANUS of chronic inflammatory and autoimmune diseases onset during COVID-19 – A systematic review of the literature. Issue 117 (February 2021) - Novelli, Lucia; Motta, Francesca; De Santis, Maria; Ansari, Aftab A.; Gershwin, M. Eric; Selmi, Carlo
Abstract: The diverse clinical manifestations of COVID-19 is emerging as a hallmark of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. While the initial target of SARS-CoV-2 is the respiratory tract, it is becoming increasingly clear that there is a complex interaction between the virus and the immune system ranging from mild to controlling responses to exuberant and dysfunctional multi-tissue directed autoimmune responses. The immune system plays a dual role in COVID-19, being implicated in both the anti-viral response and in the acute progression of the disease, with a dysregulated response represented by the marked cytokine release syndrome, macrophage activation, and systemic hyperinflammation. It has been speculated that these immunological changes may induce the loss of tolerance and/or trigger chronic inflammation. In particular, molecular mimicry, bystander activation and epitope spreading are well-established proposed mechanisms to explain this correlation with the likely contribution of HLA alleles. We performed a systematic literature review to evaluate the COVID-19-related autoimmune/rheumatic disorders reported between January and September 2020. In particular, we investigated the cases of incident hematological autoimmune manifestations, connective tissue diseases, antiphospholipid syndrome/antibodies, vasculitis, Kawasaki-like syndromes, acute arthritis, autoimmune-like skin lesions, and neurologic autoimmune conditions such as Guillain–Barré syndrome. We screened 6263 articles and report herein the findings of 382 select reports which allow us to conclude that there are 2 faces of the immune response against SARS-CoV-2, that include a benign virus controlling immune response and a many faceted range of dysregulated multi-tissue and organ directed autoimmune responses that provides a major challenge in the management of this viral disease. The number of cases for each disease varied significantly while there were no reported cases of adult onset Still disease, systemic sclerosis, or inflammatory myositis. Highlights: The immune system plays a major role in the acute progression of COVID-19. SARS-CoV-2 infection shares features with autoimmune diseases. SARS-CoV-2 can induce Guillain-Barré syndrome, arthritis, chilblain-like lesions.